OPTIMIZATION INTEGRATED MARKETING COMMUNICATION MODEL AS STRATEGIC APPROACH TO BOOST CIREBON BUSINESS LEISURE - Shela Suci Setiani; Ety Setiawati; Chondro Suryono; Yu-Fang Yen; Ratna Puspita Dewi; Abdul Khalim; Joseph Aldo Irawan (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This study centers on the strategic application of an Integrated Marketing Communication (IMC) optimization model to enhance the landscape of b-leisure in Cirebon City, West Java, Indonesia. Recognizing the city's potential, this research aims to leverage a comprehensive marketing approach to augment its appeal as a destination for both business and leisure. The primary objective of this research is to Utilize an Integrated Marketing Communication (IMC) optimization model to boost the business leisure sector in Cirebon City. By integrating various marketing channels, the study seeks to establish a cohesive and impactful communication strategy that resonates with the target audience. The research adopts a qualitative approach, using data from multiple channels; the study shows how models can be used to identify and adjust the most effective strategies accordingly. The findings of this study reveal promising outcomes in applying the IMC optimization model for enhancing business leisure in Cirebon City. The results showcase a significant positive impact on market engagement and the overall appeal of Cirebon as a dual-purpose destination. Potential limitations include data biases, the reliance on historical information, and the dynamic nature of consumer preferences, which may influence the interpretation of the findings. The originality lies in adapting this Model to a specific regional setting, offering practical insights for academics and practitioners in destination marketing.